White Matter Changes on Diffusion Tensor Imaging in the FINGER Randomized Controlled Trial - Stephen Ruth; Solomon Alina; Ngandu Tiia; Levälahti Esko; Rinne Juha O.; Kemppainen Nina; Parkkola Riitta; Antikainen Riitta; Strandberg Timo; Kivipelto Miia; Soininen Hilkka; Liu Yawu; et al. (IOS PRESS, 2022)
Background: Early pathological changes in white matter microstructure can be studied using the diffusion tensor imaging (DTI). It is not only important to study these subtle pathological changes leading to cognitive decline, but also to ascertain how an intervention would impact the white matter microstructure and cognition in persons at-risk of dementia.Objectives: To study the impact of a multidomain lifestyle intervention on white matter and cognitive changes during the 2-year Finnish Geriatric Intervention Study to prevent Cognitive Impairment and Disability (FINGER), a randomized controlled trial in at-risk older individuals (age 60-77 years) from the general population.Methods: This exploratory study consisted of a subsample of 60 FINGER participants. Participants were randomized to either a multidomain intervention (diet, exercise, cognitive training, and vascular risk management, n = 34) or control group (general health advice, n = 26). All underwent baseline and 2-year brain DTI. Changes in fractional anisotropy (FA), diffusivity along domain (F1) and non-domain (F2) diffusion orientations, mean diffusivity (MD), axial diffusivity (AxD), radial diffusivity (RD), and their correlations with cognitive changes during the 2-year multidomain intervention were analyzed.Results: FA decreased, and cognition improved more in the intervention group compared to the control group (p < 0.05), with no significant intergroup differences for changes in F1, F2, MD, AxD, or RD. The cognitive changes were significantly positively related to FA change, and negatively related to RD change in the control group, but not in the intervention group.Conclusion: The 2-year multidomain FINGER intervention may modulate white matter microstructural alterations.